2013
DOI: 10.3109/21681805.2013.817482
|View full text |Cite
|
Sign up to set email alerts
|

Dabigatran for thromboprophylaxis after robotic assisted laparoscopic prostatectomy: Retrospective analysis of safety profile and effect on blood coagulation

Abstract: RALP activates coagulation, and thromboprophylaxis for high-risk patients even after minimally invasive surgery may be beneficial. Orally administered dabigatran after discharge from hospital appears safe for venous thromboembolism prophylaxis after RALP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The literature about risk of bleeding in gynecology is limited to postsurgery complication in a single case (Wagner et al , ). In urology, data about postoperative bleeding is reported as a secondary outcome reaching a rate of 2.3% (Saily et al , ). In urgent care and anesthesiology, the risk of bleeding is extremely important, but a recent publication addressing the topic of perioperative management of new direct oral anticoagulants in these settings described it as ‘a question without answers’ (Ferrandis et al , ).…”
Section: Risk Of Bleedingmentioning
confidence: 99%
“…The literature about risk of bleeding in gynecology is limited to postsurgery complication in a single case (Wagner et al , ). In urology, data about postoperative bleeding is reported as a secondary outcome reaching a rate of 2.3% (Saily et al , ). In urgent care and anesthesiology, the risk of bleeding is extremely important, but a recent publication addressing the topic of perioperative management of new direct oral anticoagulants in these settings described it as ‘a question without answers’ (Ferrandis et al , ).…”
Section: Risk Of Bleedingmentioning
confidence: 99%
“…Data present in the literature regarding the different risk of thrombosis in patients submitted to LRP or RALP are very few. In a recent study Saily et al [ 36 ] observed that RALP activates coagulation, and thromboprophylaxis for high-risk patients even after minimally invasive surgery may be beneficial. In particular, patients undergoing RALP showed postoperatively increased levels of fibrinogen, factor VIII, d-dimer associated to a thrombocytosis, reflecting a coagulation activity.…”
Section: Discussionmentioning
confidence: 99%
“…The new oral anticoagulants have demonstrated effi cacy in preventing or treating thromboembolic disease in patients with cancer 54 and critical illnesses, 55 and in treating acute coronary syndrome [56][57][58] and other conditions. 59 However, their role in these settings is not well established. 60,61 ■ SITUATIONS TO AVOID Valvular heart disease.…”
Section: Except For Dabigatran the New Oral Anticoagulants Lack Antid...mentioning
confidence: 99%